Effects of tunnel face distance on surface settlement - Marto, A. (CRC Press/Balkema, 2016)
Underground activities such as tunnel excavation may cause soil movements around the excavation area and subsequently the ground surface. Several tunnel construction methods have been developed during the last decades and the most significant effort is to reduce the ground surface settlement. New Austrian Tunnelling Method (NATM) is one of the well-known methods which is widely used in the construction of tunnels and metro stations. This paper discusses the effects of excavation sequence and heading distance on the surface settlement induced by tunnelling in Side Gallery (SG) method, as an alternative to NATM, in Karaj Metro Tunnel (KMT) project, Iran. The Abaqus software was used to simulate the Finite Element modelling of both methods. The results showed that the removal of top head in NATM for KMT project caused 80% of the total surface settlement, but it was only 60% in SG method due to the existence of middle liner.